2005
DOI: 10.1007/s00531-005-0038-6
|View full text |Cite
|
Sign up to set email alerts
|

Precise 40Ar/39Ar dating of volcanic tuffs within the upper Messinian sequences in the Melilla carbonate complex (NE Morocco): implications for the Messinian Salinity Crisis

Abstract: International audienceThe Melilla carbonate complex (NE Morocco) is the only area of the Paleo-Mediterranean Sea where volcanic activity was present throughout most of the Messinian. 40Ar/39Ar dating of volcanic tuffs interbedded within the upper Messinian sedimentary deposits, known as the Terminal Carbonate Complex (TCC), yields accurate ages of paleoenvironmental and sea-level changes related to the Messinian Salinity Crisis. The new chronologic data (1) provide an average of 5.95– 5.99 Ma for the base of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Rifian Corridor sedimentation started at ca.8 Ma and was characterised by grey and blue fossiliferous marl with variable terrigenous intercalations (Wernli, 1988;Krijgsman et al, 1999;Gelati et al, 2000;Hilgen et al, 2000, Dayja, 2002Barhoun and Bachiri Taoufiq, 2008;Achali et al, 2016). Evidence for carbonate factories is abundant on the Mediterranean side of the seaway (e.g., Saint-Martin and Cornée, 1996;Münch et al, 2006), but scarcer in the central areas of the corridor, where published data are limited to the Gulf of Skoura, on the southeastern margin of the Saiss Basin (Charrière and Saint-Martin, 1989;Saint-Martin and Charrière, 1989;Fig. 1).…”
Section: Geological Settingmentioning
confidence: 99%
“…Rifian Corridor sedimentation started at ca.8 Ma and was characterised by grey and blue fossiliferous marl with variable terrigenous intercalations (Wernli, 1988;Krijgsman et al, 1999;Gelati et al, 2000;Hilgen et al, 2000, Dayja, 2002Barhoun and Bachiri Taoufiq, 2008;Achali et al, 2016). Evidence for carbonate factories is abundant on the Mediterranean side of the seaway (e.g., Saint-Martin and Cornée, 1996;Münch et al, 2006), but scarcer in the central areas of the corridor, where published data are limited to the Gulf of Skoura, on the southeastern margin of the Saiss Basin (Charrière and Saint-Martin, 1989;Saint-Martin and Charrière, 1989;Fig. 1).…”
Section: Geological Settingmentioning
confidence: 99%
“…6) record alternations of volcanic ashes interbedded with diatomites and marls that grade up and laterally into reef carbonates ( Fig. 2; Cornée et al 2002;Cunningham & Collins 2002;Cunningham et al 1994;Cunningham et al 1997;Münch et al 2001;Münch et al 2006;Roger et al, 2000;Saint Martín & Cornée 1996;Saint Martín et al 1991;Van Assen et al 2006;Azdimousa et al 2006;Barhoun & Wernli 1999). Where the sections have been astronomically tuned and/or Ar/Ar dated, the resulting interpretation suggests that cyclic sedimentation began around 6.84 Ma (Van Assen et al, 2006).…”
Section: Mediterranean Offshore Succession Adjacent To the Corridorsmentioning
confidence: 99%
“…The overlying Sinis Limestone and Torre del Sevo Limestones formations were deposited during a second highstand. Thus, the two formations represent the Terminal Carbonate Complex and were deposited at the beginning of the MSC (e. g. Münch et al, 2006), as previously suggested by Cherchi et al (1978).…”
Section: Geological Settingmentioning
confidence: 77%
“…These marginal evaporites are linked to an earlier and smaller drawdown (around 5.96 Ma, Clauzon et al, 1996;Münch et al, 2006;or 6.88 Ma, Butler et al, 1995). This early drawdown has been caused by the shallowing of the corridors shortly before the Crisis, near the Tortonian-Messinian boundary (Benson et al, 1991) or around 6.8 to 5.77 Ma (Garcès et al, 1998;Krijgsman et al, 2000;Cornée et al, 2006).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation